2009
DOI: 10.1021/ja902686h
|View full text |Cite
|
Sign up to set email alerts
|

Internal Return of Carbon Dioxide in Decarboxylation: Catalysis of Separation and 12C/13C Kinetic Isotope Effects

Abstract: It has been proposed that the decarboxylation of mandelylthiamin, the adduct of benzoylformate and thiamin, is uniquely catalyzed by protonated pyridines through a preassociation mechanism in which proton transfer competes with the internal return of carbon dioxide. Application of this mechanism suggests that the observed primary (12)C/(13)C kinetic isotope effect in the absence of catalyst is reduced in magnitude because diffusion of carbon dioxide is partially rate-determining. Where proton transfer blocks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Together, we developed methods to measure the CKIE under various conditions [48]. Mundle's results established that protonated pyridine does indeed produce an observable increase in the CKIE, consistent with this reaction model and its risky prediction [16]. Objections to this mechanism (based on computations) suggested in one instance that the role of pyridine is to lower the energy of the transition state without any comment on the critical issue of the effect of the catalyst of the magnitude of the CKIE [49].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Together, we developed methods to measure the CKIE under various conditions [48]. Mundle's results established that protonated pyridine does indeed produce an observable increase in the CKIE, consistent with this reaction model and its risky prediction [16]. Objections to this mechanism (based on computations) suggested in one instance that the role of pyridine is to lower the energy of the transition state without any comment on the critical issue of the effect of the catalyst of the magnitude of the CKIE [49].…”
Section: Introductionsupporting
confidence: 67%
“…However, our recent observations of catalysis of decarboxylation in solution suggested that the departure of CO 2 itself can be the source of low reactivity that is overcome by alternative pathways that promote separation of the products [12,13]. With that knowledge, we can consider previously undiscovered routes for catalyzing decarboxylation [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A likely explanation to consider for the effect of D-GAP is that decarboxylation is reversible 2123 and CO2 release from the enzyme is potentiated by D-GAP binding. Several reports by Kluger et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that in a reaction that is slowed by recombination, a preassociated acid that quenches the carbanion (Scheme 1) increases the overall rate. 7 Recent reports of computational analyses dispute the possibility that the catalysis occurs by protonation in competition with recombination of CO 2 . 9,10 One of those reports concludes that the catalysis arises from stabilization of the transition state through complexation rather than proton transfer.…”
Section: * S Supporting Informationmentioning
confidence: 99%